"Anemia and Response to Neoadjuvant Chemotherapy in Breast Cancer Patients". (9th August 2021) - Danzinger, Sabine; Fügerl, Alexandra; Pfeifer, Christian; Bernathova, Maria; Tendl-Schulz, Kristina; Seifert, Michael
Abstract: We analyzed the effect of anemia on tumor response of patients with primary invasive breast cancer (BC) receiving neoadjuvant chemotherapy (NACT). The patient collective was very homogenous; finally, 74 BC patients with identical medication and duration of NACT were enrolled. After completion of NACT, 49 patients (66.2%) had a post-NACT Hb level <12 g/dl. In the anemic group, we found a tendency of lower median tumor response compared to nonanemic patients at this time (15 versus 17 mm, retrospectively, p = 0.18). Age at diagnosis significantly correlated with the difference of Hb [before initiation – after completion of NACT] (correlation coefficient = 0.40, p < 0.001).